(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
“Ratéb Dôda Idi” is a traditional lullaby passed on from generation to generation in Aceh society of Indonesia, as one of the mediums for cultivating religious and other important values in children. There is a scarcity of studies that specifically examine the lullaby concerning its kinds of compassion based on the religious teachings of Islam. Hence, this study intends to fill in the gap by probing the kinds of compassion embedded in “Ratéb Dôda Idi” and how religion plays a role in immersing these teachings. It employed an ethnographic case study to analyse the verses by interviewing 17 Acehnese elders to obtain data. The results showed that the lullabies contain five kinds of compassion essential to Acehnese society – compassions for parents, teachers, society, nature and the homeland. It is necessary to preserve this tradition of local wisdom because language, religion and cultural heritage reflect and shape the values, beliefs and aspirations that define and keep their integrity as an Acehnese society. This kind of study thus helps our understanding of the values expressed in lullabies from many cultures and these beliefs are mirrored in the society of the singers (i.e., speakers).